Uplink Interference Analysis between LEO and GEO Systems in Ka Band - Xu, Pin; Wang, Cheng; Yuan, Jun; Zhao, Yuan; Ding, Rui; Wang, Weidong (2018 IEEE 4th International Conference on Computer and Communications (ICCC), 2018)
The frequency reuse of Geostationary Orbit (GEO) satellite systems and Low Earth Orbit (LEO) satellite systems within the same spectrum to enhance the spectrum efficiency in Ka band has attracted great interests in satellite communication research lately. However, coexistence interference will occur when different satellite systems share the same spectrum. Therefore, it is crucial to analyze the coexistence interference and study the interference mitigation techniques. In this paper, uplink interference between GEO satellite system and LEO satellite system has been analyzed, including the worst-case of uplink interference and the effects of an exclusion angle on mitigating coexistence interference. Adopting the OneWeb system as a use case, the interference analysis results are given by simulation.